Mental health, legal capacity, and human rights / edited by Michael Ashley Stein, Faraaz Mahomed, Vikram Patel, Charlene Sunkel ; editorial assistant Juliana Lynn Restivo. - Stein, Michael Ashley; Mahomed, Faraaz, 1985-; Patel, Vikram; Sunkel, Charlene; Restivo, Juliana Lynn (Cambridge University Press, 2021)
Since adoption of the Convention on the Rights of Persons with Disabilities and the interpretive General Comment 1, the topic of legal capacity in mental health settings has generated considerable debate in disciplines ranging from law and psychiatry to public health and public policy. With over 180 countries having ratified the Convention, the shifts required in law and clinical practice need to be informed by interdisciplinary and contextually relevant research as well as the views of stakeholders. With an equal emphasis on the Global North and Global South, this volume offers a comprehensive, interdisciplinary analysis of legal capacity in the realm of mental health. Integrating rigorous academic research with perspectives from people with psychosocial disabilities and their caregivers, the authors provide a holistic overview of pertinent issues and suggest avenues for reform.